Microwave-Assisted Tissue Preparation for Rapid Fixation, Decalcification, Antigen Retrieval, Cryosectioning, and Immunostaining - Kazuo Katoh (International Journal of Cell Biology)
Microwave irradiation of tissue during fixation and subsequent histochemical staining procedures significantly reduces the time required for incubation in fixation and staining solutions. Minimizing the incubation time in fixative reduces disruption of tissue morphology, and reducing the incubation time in staining solution or antibody solution decreases nonspecific labeling. Reduction of incubation time in staining solution also decreases the level of background noise. Microwave-assisted tissue preparation is applicable for tissue fixation, decalcification of bone tissues, treatment of adipose tissues, antigen retrieval, and other special staining of tissues. Microwave-assisted tissue fixation and staining are useful tools for histological analyses. This review describes the protocols using microwave irradiation for several essential procedures in histochemical studies, and these techniques are applicable to other protocols for tissue fixation and immunostaining in the field of cell biology.